Struktur Soteriologi Paulus dalam Roma 1:16-17: Relasi Injil, Kebenaran Allah, dan Iman - Bryllyan Erhuero Liliefna; Irenza Arta Nauli Manurung; Junette Hendrika Martha Manusiwa (Sekolah Tinggi Teologi Injili Indonesia Yogyakarta, 2026)
This study aims to reconstruct Paul’s soteriological structure in Romans 1:16–17 through an analysis of the relationship between the gospel, the power of God, the righteousness of God, faith, and salvation. Although Romans 1:16–17 is recognized as the theological thesis of the Epistle to the Romans, previous studies have tended to discuss these concepts separately, so that the theological connections between them have not been systematically explained. Based on a qualitative method grounded in a literature review, this study demonstrates that Romans 1:16–17 contains a coherent soteriological structure, wherein the Gospel serves as the means of revealing God’s power, God’s power manifests God’s righteousness, God’s righteousness is received through faith, and faith leads humanity to salvation. The novelty of this study lies in the formulation of a structural model of Paul’s soteriology that integrates these five elements into a single theological unity.